Multiple measures : benchmarking quality assessment tasks to facilitate interdisciplinary learning in the creative arts and humanities : final report. - Tregloan, Kate; Wise, Kit; Forsyth, Graham; Baker, Su; Symons, Debbie (Dept of Education and Training, 2017)
Final report from a project that was focused on an interdisciplinary approach to creative arts and humanities education in universities. The project: identified the objectives and core value of interdisciplinary (ID) learning by reviewing current activities and ambitions in this area; contributed to a shared understanding of ID assessment standards (national + international relevance); improved the equitable comparison of ID assessment across higher education institutions; enhanced the ability of individual teaching staff to develop criteria for ID assessment tasks, articulated these criteria to students, and graded student work according to clearly identified and constructively aligned external points of reference; and provided resources to enhance training of teaching staff, by including attention to grading of student work and provision of guidance and feedback consistent with intended learning outcomes.